2021
DOI: 10.1038/s41467-020-20456-x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic quantum causal models

Abstract: Causal reasoning is essential to science, yet quantum theory challenges it. Quantum correlations violating Bell inequalities defy satisfactory causal explanations within the framework of classical causal models. What is more, a theory encompassing quantum systems and gravity is expected to allow causally nonseparable processes featuring operations in indefinite causal order, defying that events be causally ordered at all. The first challenge has been addressed through the recent development of intrinsically qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
114
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(117 citation statements)
references
References 61 publications
3
114
0
Order By: Relevance
“…1 is independently obtained in Ref. [28] by Barrett et al They present it as a main result and use the same fact as Thm. 4 in their proof.…”
Section: Implications Of the Main Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…1 is independently obtained in Ref. [28] by Barrett et al They present it as a main result and use the same fact as Thm. 4 in their proof.…”
Section: Implications Of the Main Resultsmentioning
confidence: 59%
“…[27] proving the decomposition of the reversibility preserving superchannels and Ref. [28] on one of our implications on the equivalence between causal separability and unitarily extendibility of bipartite processes. Reference [27] exploits the decomposition derived in Ref.…”
Section: Note Addedmentioning
confidence: 99%
See 1 more Smart Citation
“…The second is the existence of parallel compositions of 1 This has to be distinguished from the recent surge in interest in indefinite causal order (ICO) [6,7,8,9], which also goes beyond standard quantum circuits in a different way. Even though the framework presented here would have natural applications to the study of ICO [10], it is important to emphasise that the features that differentiate it from standard quantum circuits are not of the same kind as those that give rise to ICO; all the constructions under study in the present work display a definite causal order.…”
Section: Introductionmentioning
confidence: 99%
“…A second line of research, that of causal decompositions [29,30,31,10] (described more comprehensively in Section 2.2), aims at probing the equivalence between the compatibility of a unitary channel with a given causal structure, and the existence of a decomposition for this channel along a given unitary circuit in which this causal structure is made obvious. In this context, it was found that, in order to prove such an equivalence in some cases, one has to consider decompositions in which some of the unitary channels satisfy sectorial constraints and are parallelly composed in a non-trivial way.…”
Section: Introductionmentioning
confidence: 99%